Effect of dietary n-3 polyunsaturated fatty acids on antioxidant defense and sperm quality in rainbow trout (Oncorhynchus mykiss) under regular stripping conditions - Koprucu, Kenan; Yonar, Muhammet Enis; Ozcan, Sinan (Elsevier, 2015)
This study examined the effect of dietary n-3 polyunsaturated fatty acids (PUFA) on malondialdehyde (MDA), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and reduced glutathione (GSH) levels; semen and liver fatty acid compositions; and spermatological values (semen volume and pH, sperm density, percentage and duration of sperm motility) in rainbow trout (Oncorhynchus mykiss) under regular stripping conditions. For this purpose, one control and two experimental diets were prepared as isonitrogenous and isocaloric. The control diet did not contain n-3 PUFA. However, the D1 and D2 diets were supplemented with n-3 PUFA concentrated anchovy oil at a 1% and 2% level, respectively. The n-3 PUFA content in the semen and liver, semen volume, initial sperm motility, duration of 50% sperm motility, total duration of sperm motility and sperm density values of the control fish fed the n-3 PUFA-deficient diet were decreased and were accompanied by a reduction of the antioxidant defense (SOD, CAT, GSH-Px and GSH) and an elevation of MDA in the blood, gonad, liver and kidney at all of the sampling periods (P< 0.01 for each case). However, the effects of the sampling period on the MDA and antioxidant defense values in the blood, gonad, liver and kidney of the control diet fish (with the exception of the GSH and GSH-Px activities) and the D1 and D2 diet fish were not significant (P > 0.01). However, supplementation with n-3 PUFA protected the fish from these adverse effects. The modulations were clearly observed in the fish fed the D2 diet because they were under lower oxidative stress, as indicated by MDA. The increased enzyme activity corresponds with the physiological mechanisms combating the elevation of free radicals under oxidative stress. The highest n-3 PUFA levels in the semen and liver and spermatological values were obtained from the fish fed the D2 diet at all of the sampling periods. On the other hand, the effects of the sampling stage on the spermatological values of the fish fed the D1 and D2 diets were not significant (P > 0.01). However, the effects of the sampling stage in the fish fed the control diet on these values (with the exception of semen pH) were significant (P < 0.01). In conclusion, the addition and balance of n-3 PUFA in the diet of broodstock fish can improve sperm quality and ultimately cause successful reproduction. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Antioxidant enzymes; n-3 PUFA; Oxidative stress; Rainbow trout; Sperm quality